2017
DOI: 10.1136/bmjopen-2017-018398
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood health in Bielefeld, Germany (BaBi study): study protocol of a social-epidemiological birth cohort

Abstract: IntroductionThe heterogeneity among the German population is increasing. Sociodemographic differentials (eg, in education and migrant status) have been associated with health disparities. Life course studies show that a considerable part of these disparities is determined by exposures during pregnancy and early childhood. The BaBi study was established in 2012 to investigate the production of health disparities from foetal life to childhood in the city of Bielefeld, Germany.Methods and analysisBetween 2013 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
(6 reference statements)
0
24
0
1
Order By: Relevance
“…This analysis is based on data collected in the BaBi (Babys in Bielefeld) birth cohort study [16]. Over a three-year period (2013-16), we recruited 977 women and conducted standardized computer-assisted personal interviews (CAPI) during pregnancy (n = 305) or shortly after birth (n = 672).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis is based on data collected in the BaBi (Babys in Bielefeld) birth cohort study [16]. Over a three-year period (2013-16), we recruited 977 women and conducted standardized computer-assisted personal interviews (CAPI) during pregnancy (n = 305) or shortly after birth (n = 672).…”
Section: Methodsmentioning
confidence: 99%
“…A limitation of our analyses is that the BaBi study sample is skewed toward more educated and wealthier women. This is partly due to the recruitment strategy which started with a passive recruitment phase during which flyers and response boxes were left in gynecologists and midwifes practices [16]. Such recruitment is more likely to attract better-educated participants than active recruitment where women are directly approached by the interviewers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline data included modules on pregnancy-related health, health care and behaviours and on socioeconomic and migration backgrounds. More details about the aims and designs of those studies can be found elsewhere (Brenne et al 2015;Spallek et al 2017). The participants were introduced to the study by researchers in one-to-one conversations during which were answered any questions they may have had.…”
Section: Methodsmentioning
confidence: 99%
“…They, however, did not perform further analyses aiming to identify factors explaining this difference. Building on this work, there is currently an opportunity to explore further those issues within the German context by analysing the combined baseline data of two German cohort studies: the aforementioned Berlin perinatal study (Brenne et al 2015) and the BaBi birth cohort study based in Bielefeld (Spallek et al 2017). While both studies are comparable in their designs and intent, they were conducted in environments with different socioeconomic characteristics and have rather different participants' profiles.…”
Section: Introductionmentioning
confidence: 99%